2000
DOI: 10.1074/jbc.275.8.5395
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Heme Oxygenase in Neuronal Cells, the Possible Interaction with Tau

Abstract: Increased expression of heme oxygenase-1 (HO-1) is a common feature in a number of neurodegenerative diseases. Interestingly, the spatial distribution of HO-1 expression in diseased brain is essentially identical to that of pathological expression of tau. In this study, we explored the relationship between HO-1 and tau, using neuroblastoma cells stably transfected with sense and antisense HO-1 constructs as well as with the vector alone. In transfected cells overexpressing HO-1, the activity of heme oxygenase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
98
1
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 176 publications
(106 citation statements)
references
References 38 publications
6
98
1
1
Order By: Relevance
“…Therefore, the regulation of tau phosphorylation in the adult mammalian brain appears to represent a naturally occurring process that is associated with neuroprotective mechanisms [70]. In support of this, it has been observed that cellular antioxidant induction and tau expression are opposing [56,72], suggesting that the reduced oxidative damage in neurons showing tau accumulation [73] might be a direct consequence of an antioxidant function of phosphorylated tau [51,54].…”
mentioning
confidence: 58%
“…Therefore, the regulation of tau phosphorylation in the adult mammalian brain appears to represent a naturally occurring process that is associated with neuroprotective mechanisms [70]. In support of this, it has been observed that cellular antioxidant induction and tau expression are opposing [56,72], suggesting that the reduced oxidative damage in neurons showing tau accumulation [73] might be a direct consequence of an antioxidant function of phosphorylated tau [51,54].…”
mentioning
confidence: 58%
“…Heme oxygenase-1 (HO-1) is an antioxidant enzyme that degrades heme into biliverdin, iron and carbon monoxide and is one of the most sensitive and selective indicators of the cellular oxidative stress response. It has been shown that brains of AD patients present an increase of both HO-1 mRNA and protein [58,65] which co-localizes and parallels the expression of the altered form of tau characteristic of AD [76,77].…”
Section: −•mentioning
confidence: 99%
“…Hsps serve as molecular chaperones and among the various Hsps, Hsp32 (also known as HO-1) and Hsp72 have been recently demonstrated to play neuroprotective role against oxidative stress (20). HO-1 is the inducible form of a group of enzymes that catalyze heme degradation to form the antioxidant biliverdin and CO (22). Overexpression of human HO-1 gene has been shown to result in a stable increase of HO activity associated with neuroprotection against oxidative injury (23).…”
Section: Introductionmentioning
confidence: 99%